Research on the Construction and Development Prospect of Aided Business English Teaching System Based on Computer Multimedia Technology - Zhang, Baicheng (Mobile information systems, 2022)
The intervention of multimedia technology has had a profound impact on education, which has led to the renewal of educators’ ideas, the renewal of educational means, and the renewal of educational forms. To some extent, the influence of multimedia technology on educational technology has opened a new chapter in educational reform. It can be said that the powerful advantages of multimedia education technology promote the pace of teaching reform and conform to the needs of the development of the times. This paper mainly analyzes the research on the construction and development prospects of the business English teaching system based on computer multimedia technology, uses the computer vision technology to collect teaching information, and then uses VR for teaching. Computer vision mainly studies how to use video sensing devices and computers to simulate the human visual system to collect and process external visual information, so that machines have the same visual ability as humans and even have the ability to “think.” Through virtual teaching design and research virtual teaching methods, combined with the characteristics of business English subjects, the computer vision technology is connected with business English course teaching to develop new teaching methods for business English subjects; analyze the teaching purpose, content, and feasibility; and investigate the difficulties and needs of students in business English subject learning to determine the educational methods in a smart environment application in actual business English teaching. This article uses literature research method, questionnaire method, experimental research method, and interview method to conduct research. At the same time, this article also uses Maya and other software multidimensional design functions to explain the educational methods in a smart environment; set up a virtual hypothesis experiment to objectively analyze the development prospects of educational methods in an intelligent environment in business English teaching from the aspects of curriculum teaching, classroom effects, and learner efficiency; and summarize the parts that need improvement.